Early Adolescent Critical Consciousness Development in the Age of Trump. Issue 3 (May 2020) - Kennedy, Heather; Matyasic, Savahanna; Schofield Clark, Lynn; Engle, Corey; Anyon, Yolanda; Weber, Margo; Jimenez, Carlos; Osiemo Mwirigi, Mike; Nisle, Stephanie
Political elections have been shown to influence youth civic development. The election of Donald Trump is historic and has elevated precarity for people of color and immigrants, yet we know little about how young people with these identities experienced this potentially catalytic event. Using ethnographic methods, we examined youth and adult discussions that occurred during youth participatory action research in four sites of one after-school program between October 2016 and May 2017, to investigate how the development of critical consciousness occurs among early adolescent youth of color in the context of catalyzing political events. We identified emergent patterns in how young people (a) engaged in critical reflection, (b) weighed political efficacy, and (c) considered engagement in critical action in the wake of Trump's election. The data revealed that young people's critical consciousness development ranged from basic to advanced levels. This research highlights the ways that politically catalytic events shape critical consciousness development among early adolescents of color.